Steganography with Digital Image Technique On Integer Wavelet Transform Cielab - Alhaziyah R M; Rizal U (Bandar Lampung University (UBL), 2017)
Remarkable progress in the field of information technology and telecommunications led to the emergence of demand for secure communication environment and have privacy. Steganography is a method used to disguise the presence of confidential information, making it difficult to detect its presence by people who do nothave the authority for the information. Additionally, steganography can be applied to multimedia such as text, images, audio / video and protocols. Problems often arise in research on steganography, among others, the low capacity of concealment, less pharmaceutics stego-image, as well as the poor quality of stego-image is generated. This study aims to create a digital image steganography safe, sturdy, has a high masking capacity and has good imperceptibility, so the fidelity and recovery capabilities will be good anyway. The method proposed in this study manggabungkan Integer Wavelet Transform technique that aims to increase the capacity of concealment Furthermore this research is done on the CIELAB color space, where CIELAB can produce digital images with high compression range and a small color deviations on wavelet transform. In the watermarking technique in wavelet domain, CIELAB has the most excellent robustness compared with other color spaces. For security measures, used steganalyzer's ROC performance and PSNR of the quality of stego-image is generated